Intensifikasi Website yang Digunakan untuk Penerimaan Pendaftaran Siswa Baru di SMP 4 Mangarabombang sebagai Bentuk Adaptasi Pada Revolusi Industri 4.0 - Marwan Ramdhany Edy; Wishmoon Sojum Saidar; Reski Aulia Mansyur; Muna Maulida (Indonesian Technology and Education Journal, 2024)
One of the educational institutions whose primary objective is to offer junior high school education services is SMP 4 Mangarabombang. This educational institution makes use of information and technological advances to provide educational services, particularly during the fourth industrial revolution, which has had a substantial impact on education as well as other spheres of life and the workplace. It seeks to improve kids' and their parents' future-relevant satisfaction and knowledge. One illustration is the ability to admit new students via a website. A website acts as a platform for information that is not constrained by time or place. The website's layout for this information system is intended to make it easier to provide information about the system can consider providing reports to improve more efficient information distribution, student enrollment, streamlining the registration process, and ensuring the security of prospective students' data